Discourse Analysis and Distance Factors on Determine News Sources about Papua Riots in Online Media - Tobing, Melati Mediana; Ibrahim, Nor Idayu (Jurnal The Messenger, 2024)
Introduction: The Papua riots in Indonesia that happened in 2019 have received global viewers and national media attention. The national media reports the events through different sources. In another perspective, the distance factor had become an important variable in determining the source or informant, especially for a medium far from the scene. The research aims: first, exploring the discourse about dominant media and subdominant online media in covering issues, and secondly, have another comprehend about informant selection factors according to the distance between online media in the local area and capital city area. Methods: Through comparison of dominant and subdominant online media in Indonesia, this research has been describing events and social actors portrayed, by Theo Van Leewen's method of critical discourse analysis. This research been used 45 news sites Kompas.com and 20 news Tabloidjubi.com which are related to the 2019 Papua riots during August 19 to August 24, 2019. Findings: With analysis table as a guarantor of validity the research have been display all the news samples represented by five categorizations of themes. Text has been interpreting as a verification of the validity of the text through the perspective of the reader with Van Leewen's critical discourse, namely exclusion and inclusion. Originality: It was novelty that both online media potentially could be able more exploring their sources of information to expand their reader distance segmentation. In addition, online media should have new perspective to be an origin sources across markets for global viewers.